Young women and their role in sustainable fashion: consumer awareness and education and their influence in sustainable purchase habits - Madeira, Sara Afonso (2022)
The present research paper was conducted with the goal of studying how young women interact with Sustainable Fashion, regarding both their level of knowledge and interest concerning the existing options when acquiring clothing items. Young women are a promising target for SF, showing interest in both fashion and sustainability, at a time when fashion companies have been increasing their sustainability measures to address increasingly conscious consumers. This study was based on the qualitative research and thematic analysis of 23 in-depth interviews of women aged 19 to 27 years old. The main conclusions drawn are that young women are interested in SF, but there is a significant lack of concrete knowledge regarding the subject, especially when the individuals do not partake in research from their own initiative. They also believe the education of consumers is crucial for SF to become more mainstream. Therefore, brands should take advantage of their advertisement of SF and focus on creating conscious awareness so consumers will opt to invest in sustainable products when purchasing clothing items.